2018
DOI: 10.15252/embr.201745494
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric epigenetic response mediated by Gadd45a regulates stem cell aging and lifespan

Abstract: Progressive attrition of telomeres triggers DNA damage response (DDR) and limits the regenerative capacity of adult stem cells during mammalian aging. Intriguingly, telomere integrity is not only determined by telomere length but also by the epigenetic status of telomeric/sub-telomeric regions. However, the functional interplay between DDR induced by telomere shortening and epigenetic modifications in aging remains unclear. Here, we show that deletion of Gadd45a improves the maintenance and function of intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
(131 reference statements)
0
11
0
1
Order By: Relevance
“…Telomere integrity is also under the control of the epigenetics dynamics of the telomeric/subtelomeric area. Experiments in telomerase-deficient mice (G3Terc -/-) showed that the deletion of the growth arrest and DNA damage-inducible protein 45 alpha (Gadd45a), critical for epigenetic gene activation via repair-mediated DNA demethylation, markedly reduced the DDR and improved the function and regenerative capability of IESCs and in so doing extended the life span of G3Terc -/-mice (Diao et al 2018).…”
Section: 2-effect Of Ageing On the Iescmentioning
confidence: 99%
“…Telomere integrity is also under the control of the epigenetics dynamics of the telomeric/subtelomeric area. Experiments in telomerase-deficient mice (G3Terc -/-) showed that the deletion of the growth arrest and DNA damage-inducible protein 45 alpha (Gadd45a), critical for epigenetic gene activation via repair-mediated DNA demethylation, markedly reduced the DDR and improved the function and regenerative capability of IESCs and in so doing extended the life span of G3Terc -/-mice (Diao et al 2018).…”
Section: 2-effect Of Ageing On the Iescmentioning
confidence: 99%
“…Consistent with this, shortening of telomeres was associated with differentiation. Telomere attrition was associated with loss of stemness markers in cardiac progenitor cells isolated from adult human heart failure cases (92); unstable differentiation was observed in ESCs with telomere dysfunction because of critically shorter telomeres (41); regenerative capacity of stem cells declined because of progressive telomere attrition in aging cells (93); and reduced proliferation and differentiation to osteoblasts was observed in mesenchymal stromal cells isolated from adults compared with those isolated from children, suggesting the impact of telomere attrition (94). On the other hand, longer life span was observed in cells that differentiated from human ESCs possessing relatively long telomeres (28) and cardiomyocytes differentiated with improved efficacy from iPSCs that had relatively long telomeres (26).…”
Section: Telomere Elongation and Pluripotencymentioning
confidence: 99%
“…As the number of cell divisions increases, telomeres gradually shorten. When telomeres are too short that DNA is unable to continue to replicate and chromosome stability is at risk, stem cell senescence is induced, resulting in cell division stagnation, inability to continue to replicate, and eventually apoptosis [15]. Therefore, telomere shortening is a common sign of senescence in all cells, including stem cells.…”
Section: Telomere and Telomerasementioning
confidence: 99%
“…Depletion of GADD45a promotes chromatin condensation in the subtelomere regions. GADD45a knockout can improve the function of intestinal stem cells and extend the lifespan of telomerase-deficient mice (G3Terc−/−) [15].…”
Section: Telomere and Telomerasementioning
confidence: 99%